Regional Financial Efficiency Ratio and Suitability in Improving Regional Development of West Aceh Regency - Yasrizal, Yasrizal; Mahrizal, Mahrizal; Wahyuningsih, Yayuk Eko; Harmaini, Harmaini; Syafrizal, Syafrizal (Teunuleh Publisher, 2023)
In the analysis of the financial condition of Aceh Barat Regency, it was revealed that significant dependence on Central Transfers, especially through the General Allocation Fund (DAU) and the Special Allocation Fund (DAK), creates challenges in achieving stable financial independence. Although Locally Generated Revenue (PAD), such as regional taxes and levies, contributes to the revenue, the fluctuations indicate the complexity and risk in achieving financial balance. Diversifying revenue sources has become a primary focus to address dependence on natural resources and the fisheries sector, as well as external fluctuations. Optimizing regional taxes, levies, and developing the tourism sector are key strategies to strengthen Locally Generated Revenue. Moreover, the analysis of the Regional Financial Efficiency Ratio (REKD) indicates characteristics of inefficiency or inefficiency during the 2011-2022 period, highlighting the need for improvements in budget management and revenue collection. The Compatibility Ratio, which shows an increase in Operating Expenditure and a tendency to decrease Capital Expenditure, underscores the need to achieve a better balance between long-term investment and operational activities. Therefore, Aceh Barat Regency needs to take proactive steps in enhancing financial efficiency, diversifying income, and allocating funds wisely to achieve sustainable economic growth and financial stability.